The Genetics of Adverse Drug Outcomes in Type 2 Diabetes: A Systematic Review - Baye, Assefa M.; Fanta, Teferi G.; Siddiqui, Moneeza K.; Dawed, Adem Y. (Frontiers in Genetics, 2021)
Background: Adverse drug reactions (ADR) are a major clinical problem accounting for significant hospital admission rates, morbidity, mortality, and health care costs. One-third of people with diabetes experience at least one ADR. However, there is notable interindividual heterogeneity resulting in patient harm and unnecessary medical costs. Genomics is at the forefront of research to understand interindividual variability, and there are many genotype-drug response associations in diabetes with inconsistent findings. Here, we conducted a systematic review to comprehensively examine and synthesize the effect of genetic polymorphisms on the incidence of ADRs of oral glucose-lowering drugs in people with type 2 diabetes. Methods: A literature search was made to identify articles that included specific results of research on genetic polymorphism and adverse effects associated with oral glucose-lowering drugs. The electronic search was carried out on 3rd October 2020, through Cochrane Library and PubMed using keywords and MeSH terms. Result: Eighteen articles consisting of 10, 383 subjects were included in this review. Carriers of reduced-function alleles of organic cation transporter 1 (OCT 1) or reduced expression alleles of plasma membrane monoamine transporter (PMAT) or serotonin transporter (SERT) were associated with increased incidence of metformin-related gastrointestinal (GI) adverse effects. These effects were shown to exacerbate by concomitant treatment with gut transporter inhibiting drugs. The CYP2C9 genotypes, *2 and *3 that are predictive of low enzyme activity were more common in subjects who experienced hypoglycemia after treatment with sulfonylureas. However, there was no significant association between sulfonylurea-related hypoglycemia and genetic variants in the ABBC8/KCNJ11. Compared to the wild type, the gain of function CYP2C8*3 allele was associated with less weight gain whereas the C allele at rs6123045 in the NFATC2 gene was significantly associated with edema from rosiglitazone treatment. Conclusion: In spite of limited studies investigating genetics and ADR in diabetes, some convincing results are emerging. Mutations in genes encoding drug transporters and metabolizing enzymes are implicated in metformin-related GI adverse effects, and sulfonylurea-induced hypoglycemia, respectively. Further studies to investigate newer antidiabetic drugs such as DPP-4i, GLP-1RA and SGLT2i are warranted. In addition, pharmacogenetic studies that account for race and ethnic differences are required.